2014
DOI: 10.4049/jimmunol.1400582
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Double-Stranded RNA Activates the NLRP3 Inflammasome via MAVS-Induced Membrane Permeabilization and K+ Efflux

Abstract: The Nlrp3 inflammasome plays an important role in inflammation by controlling the maturation and secretion of the cytokines IL-1β and IL-18 in response to multiple stimuli including pore-forming toxins, particulate matter, and ATP. Although the pathways activated by the latter stimuli lead to a decrease inintracellular K+concentration,which is required for inflammasome activation,the mechanism by whichmicrobial RNA activates Nlrp3, remains poorly understood. Here we found that cytosolic poly(I:C), but not tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(139 citation statements)
references
References 60 publications
(76 reference statements)
4
133
1
1
Order By: Relevance
“…PKR, a dsRNA-activated protein kinase, recently was implicated as a common regulator of inflammasome activation by E. coli RNA and polyinosinicpolycytidylic acid, as well as by a variety of other stimuli, including ATP, monosodium urate crystals, cytosolic DNA, or infection with E. coli and Salmonella (60). However, the general role of PKR for caspase-1 cleavage could not be confirmed in subsequent studies by other groups (61)(62)(63). The reason for these discrepancies remains elusive, and further studies are needed to clarify the contribution of PKR to inflammasome activation.…”
Section: Inflammasome Activation By Bacterial Rnamentioning
confidence: 53%
“…PKR, a dsRNA-activated protein kinase, recently was implicated as a common regulator of inflammasome activation by E. coli RNA and polyinosinicpolycytidylic acid, as well as by a variety of other stimuli, including ATP, monosodium urate crystals, cytosolic DNA, or infection with E. coli and Salmonella (60). However, the general role of PKR for caspase-1 cleavage could not be confirmed in subsequent studies by other groups (61)(62)(63). The reason for these discrepancies remains elusive, and further studies are needed to clarify the contribution of PKR to inflammasome activation.…”
Section: Inflammasome Activation By Bacterial Rnamentioning
confidence: 53%
“…This CARD-CARD interaction results in the dimerisation of MAVS in the mitochondria to form a protein complex called the MAVS signalosome, which enables the activation of NF-jB and the production of type I interferon (IFN). Once the innate immune system has been activated, it elicits the secretion of cytokines and chemokines, which subsequently induce the expression of adhesion molecules and costimulatory molecules to further activate the adaptive immune response [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that the MAVS protein complex is required for optimal NLRP3 recruitment and inflammasome activity (Franchi et al, 2014;Park et al, 2013;Subramanian et al, 2013). Other members of this antiviral complex are recruited to the ER-mitochondria interface to fine-tune MAVS-NLRP3 signaling, including stimulator of IFN genes (STING) ((Abdul-Sater et al, 2013;Abe and Barber, 2014), Figure 2).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%